Guideline-Based Early Detection of Chronic Obstructive Pulmonary Disease in Eight Danish Municipalities: The TOP-KOM Study - Hemmingsen, Ulla Borup; Stycke, Margit; Dollerup, Jens; Poulsen, Peter Bo (Pulmonary Medicine, 2017)
Background. Early detection of chronic obstructive pulmonary disease (COPD) and prevention of disease progression are important. Only 40% of COPD cases are diagnosed in Denmark. Recommendations for early case finding have been established. This study investigates early detection of pulmonary obstruction in a Danish municipality setting. Methods. Eight municipalities participated. Citizens fulfilling national case finding recommendations, age ≥35 years, smokers/ex-smokers/relevant occupational exposure, and at least one respiratory symptom, were invited to spirometry. Citizens with indication of pulmonary obstruction, forced expiratory volume in one second (FEV1)/forced vital capacity (FVC) < 0.70, were referred to their general practitioner (GP). Results. 1,499 citizens were examined (53.6% male, mean age 57.2 years). 44.8% were current smokers with 57% planning for smoking cessation. The citizens recorded significant airway symptoms with dyspnea being the most important (71%). The mean FEV1/FVC score was 73.54 (SD 22.84). 456 citizens (30.4%) were found to have indication for pulmonary obstruction and were referred to GP for further diagnosis. Conclusion. Early detection in Danish municipalities proved effective finding nearly 1/3 being pulmonary obstructive. It seems to be of value to have municipalities to perform case finding together with smoking cessation as a primary intervention in COPD management.